Zambia Health Sector Public : Accounting for Resources to Improve Effective Service Coverage - Picazo, Oscar F.; Zhao, Feng (Washington, DC: World Bank, 2013)
Over the past few years, three nagging problems have bedeviled Zambia's health sector: the country is falling off-track from reaching the Millennium Development Goals (MDGs), it is facing severe financing constraints on the government front, and the health and HIV/AIDS sector is increasingly being fragmented by the reemergence of global disease initiatives. This health sector pubic expenditure review (PER) seeks to assist the Government of the Republic of Zambia (GRZ) and its development partners take stock of the resources in the health sector and how these resources can be better used to produce better health services. The results of the PER are expected to be the used for a variety of purposes, including the preparation of the health sector strategic plan, and succeeding rounds of the global fund request for proposals. Policy dialogue between the Bank and GRZ, both at the macro and sector levels, can also be enriched by the PER. The PER also provides critical inputs into the Medium-Term Expenditure Framework (MTEF) process, and in the assessment of the Poverty Reduction Strategy Paper (PRSP). Likewise, the PER can provide inputs to fine-tune the process of the pooled basket funding mechanism under the sector-wide approach (SWAp).